Family Conflict and Adolescent Self-Injury: The Mediating Role of Alexithymia - Abdi, Mansour; Asadi, Nazanin Zahra (Journal of Psychosociological Research in Family and Culture, 2025)
Objective: This study aimed to examine the relationship between family conflict and adolescent self-injury, with a focus on the mediating role of alexithymia.Methods and Materials: A descriptive correlational design was employed using a sample of 396 South African secondary school students selected based on the Morgan and Krejcie sampling table. Standardized instruments were used to assess family conflict, alexithymia, and self-injurious behavior. Data were analyzed using SPSS-27 for Pearson correlation and AMOS-21 for structural equation modeling (SEM). Assumptions for normality, linearity, and multicollinearity were confirmed prior to analysis. The structural model tested both direct and indirect effects to evaluate the mediating function of alexithymia in the relationship between family conflict and self-injury.Findings: Pearson correlations showed significant positive relationships among all variables: family conflict and alexithymia (r = .42, p < .01), family conflict and self-injury (r = .34, p < .01), and alexithymia and self-injury (r = .49, p < .01). The structural model demonstrated excellent fit indices (χ²/df = 2.43, CFI = 0.96, RMSEA = 0.059). Path analysis revealed significant direct effects of family conflict on alexithymia (B = 0.43, β = .42, p < .001), alexithymia on self-injury (B = 0.38, β = .46, p < .001), and family conflict on self-injury (B = 0.19, β = .24, p = .004). The indirect effect of family conflict on self-injury through alexithymia was also significant (B = 0.16, β = .19, p < .001), confirming partial mediation.Conclusion: Findings underscore alexithymia as a critical emotional mechanism linking family conflict to self-injurious behavior in adolescents. Interventions targeting emotional awareness and family communication may help mitigate the risks associated with adolescent self-harm, especially in culturally diverse contexts.